Transformational Leaders in Handling Organizational Conflict - Asnofidal Asnofidal (Jurnal Prajaiswara, 2020)
This paper aims to describe (1) understanding of transformational leadership, (2) conflicts that affect organizational development (3) the role of transformational leaders in resolving conflicts. The discussion of the problem in this paper is carried out using a qualitative approach with a deductive method, namely discussing the problem to be studied by writing down the discussion described in general and then drawing a specific conclusion. The results of the discussion explained that; (1) Transformational leadership is a leadership style that transforms the values ​​of members personally so that they can be used as supporters or supporters of the vision and goals to be achieved by the organization being run. Leaders with this leadership style can make their subordinates or followers see the organizational goals to be achieved clearly so that they can eliminate their personal interests under the organization's interests. (2) Conflict is a serious problem that can harm an organization. Although conflicts can be beneficial and detrimental, adverse conflicts can hinder the pace of organizational development, ultimately leading to a decline in the organization. (3) The role of a leader in resolving conflicts can be done in various ways, including if the conflict occurs because it arises from within itself,h can unsettle the people associated with it.